Analysis of the Impact of ChatGPT Usage in Direct Current Physics Material on Enhancing Students' Higher-Order Thinking Skills (HOTS) during the Merdeka Belajar - Zakaria Al Farizi; Sahlan Sahlan; Erwin Prasetyo; Nadya Fitriani; Elyakim Mau Laleng; Hamzarudin Hikma Tiar; Zaina Anwar (Berkala Ilmiah Pendidikan Fisika, 2024)
This study examines the influence of using ChatGPT to enhance students' higher-order thinking Skills (HOTS), particularly within the context of the "Merdeka Belajar" (Freedom to Learn) era in Indonesia. This inquiry arises from Indonesian students' low literacy and numeracy skills, as indicated by the PISA assessment. Employing a quasi-experimental method, the research analyzes the changes in students' HOTS before and after the ChatGPT-assisted instruction intervention within the "Merdeka Belajar" curriculum framework. The study's findings reveal a significant improvement in students' HOTS within the experimental group that utilized ChatGPT, as compared to the control group. Data analysis underscores the positive impact of integrating ChatGPT into "Merdeka Belajar"-based teaching methods, substantially enhancing students' HOTS. These results align with prior literature highlighting the role of AI technology in advancing education and fostering higher-order thinking abilities. It is imperative to consider that the effective utilization of AI technology should be complemented by appropriate teaching approaches to prepare students for future challenges.  The implications of this research indicate that ChatGPT can be considered an innovative strategy to support Merdeka Belajar-based learning in Indonesia.